Sistem Pintar Penyiram Tanaman Menggunakan Teknologi IoT dan Fuzzy Inference System dalam Rangka Mewujudkan Green Campus di UIN Syarif Hidayatullah Jakarta - Nenny Anggraini; Kahfi Del Vieri; Luh Kesuma Wardhani; Ariq Cahya Wardhana; Deny Saputra (Building of Informatics, Technology and Science (BITS), 2022)
In recent years, there has been a change in climate which has had quite a negative impact on various sectors of life. The existence of extreme climate change has become a widely discussed issue, including at the university level. The academic community as agents of change should be an example of sustainable development in the campus environment. One of the efforts to realize the concept of sustainable development is to apply the Green Campus concept. Several indicators in realizing a green campus are campus management policies that are oriented towards environmental management, including activities to save water, paper, and electricity, procurement of Green Open Space (RTH), and waste management by applying the 3R principles (reduce, reuse, recycle). UIN Jakarta currently focuses on the green environment, which focuses on activities related to the conservation and maintenance of environmental quality in all energy and natural resource consumption activities. However, the frequent changes in weather, shifts in the seasons, and the size of the land that must be maintained have made watering plants unable to rely on human labor alone. Moreover, the pandemic conditions in Indonesia have caused almost all employees to work from home, so plant maintenance will be hampered for plant watering activities. In this regard, this research proposes the creation of an automated plant watering system using a Fuzzy Inference System. The experiment was carried out using input from three scenarios including soil moisture sensors, temperature sensors, and rain sensors on the output valve. From the experiments carried out, the expected valve output is in accordance with that produced by the raspberry pi. Such as when the ground is dry, the weather is not raining, and the temperature is moderate, the valve remains on according to the fuzzy rules that have been made. The results of the study noted that this tool was in accordance with what was needed and could operate properly